Evaluasi Program Pengembangan Kompetensi Berdasarkan Model Evaluasi Kirkpatrick Level 1 dan Level 2 - Susanty, Yunni (Pusat Pengembangan dan Pelatihan dan Kajian Manajemen Pemerintahan Lembaga Administrasi Negara, 2022)
The development of competencies for Civil Servants is needed in order to improve employee performance that will contribute positively to organizational performance. For this reason, competency development programs must be evaluated to see the effectiveness of their implementation. The purpose of this study is in order to evaluate competency development programs using kirkpatrick level 1 evaluation model to find out the level of satisfaction of participants and Kirkpatrick evaluation model level 2 to find out if there is an increase in participants' knowledge after participating in the competency development program. The technique of processing and analyzing data in this study uses quantitative descriptive analysis methods. Based on the results of this study, it can be concluded that participants are satisfied with the facilitator aspect and the organizer aspect and there is an increase in participants' knowledge before and after learning. The results of this research are expected to be taken into consideration to improve the quality and effectiveness of the implementation of competency development programs in the future. Keywords: evaluation; Kirkpatrick’s evaluation model; competency development